The care and feeding of 9-1-1 infrastructure: dispatcher culture as media work and infrastructural transformation. - Ellcessor, Elizabeth (Cultural Studies)
Emergency dispatchers who receive 9-1-1 calls and initiate various emergency response services perform media work that produces 9-1-1 as an infrastructural system for the public at large. This should be considered media work because it centres the interpretation of media content and navigation of multimedia systems. While a nontraditional site for the study of media work, emergency dispatch can be studied through methods of media industry and infrastructure studies in order to understand how these workers are shaped by and shaping cultural attitudes toward new media, labour, and emergency itself. Using interviews, observations, job advertisements, and management literatures, this article traces the values and practices of dispatcher culture through the sites of 'the job', 'the console', and 'the community.' Through dispatchers' media work, the logistical infrastructure of 9-1-1 is gradually transformed.